PLURALISME PRINSIPIIL DAN REFLEKSINYA TERHADAP PANCASILA - Wuysang, Chias Yohanes; Intan, Benyamin (Verbum Christi: Jurnal Teologi Reformed Injili, 2018)
This article uses theological-ethical approach to focus on the presentation of the relationship of religion and state in the concept of principled pluralism and provides a reflection on the life of the nation and state in Indonesia which has Pancasila. The theological basis used as a reference is the Reformed theology of the Neo-Calvinism wing which was pioneered by Abraham Kuyper and forwarded by ideas from Kuyperians such as Gordon Spykman, James Skillen, Jonathan Chaplin. The author will argue that Pancasila is in harmony with principled pluralism. KEY WORDS: principled pluralism, structural pluralism, confessional pluralism, Pancasila.